2001
DOI: 10.1210/jcem.86.8.7716
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and Ultradian Rhythm and Leptin Pulsatility in Adult GH Deficiency: Effects of GH Replacement

Abstract: Leptin contributes to the regulation of body weight in healthy individuals and is secreted by adipocytes in a diurnal pattern, with superimposed pulsatility. The circulating leptin concentration is increased in both normally obese and untreated adult GH deficiency, a syndrome characterized by increased adiposity. Leptin circadian rhythm is preserved in adult GH deficiency patients; however, an ultradian rhythm and pulsatility has previously not been reported. Alterations in plasma leptin concentration in obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
1
23
0
2
Order By: Relevance
“…Previous studies have demonstrated relatedness of leptin to luteinizing hormone, cortisol, and GH (3,20,21), suggesting that leptin may be an important regulator of neuroendocrine function. In this regard, studies of Chehab et al (10) and Ahima et al (1) have shown that leptin acts as a hormonal signal that conveys biological information from fat tissue to the reproductive axis and that leptin treatment accelerates the onset of puberty.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated relatedness of leptin to luteinizing hormone, cortisol, and GH (3,20,21), suggesting that leptin may be an important regulator of neuroendocrine function. In this regard, studies of Chehab et al (10) and Ahima et al (1) have shown that leptin acts as a hormonal signal that conveys biological information from fat tissue to the reproductive axis and that leptin treatment accelerates the onset of puberty.…”
Section: Discussionmentioning
confidence: 95%
“…Plasma leptin levels are inversely related to those of ACTH in young men (20) and display pattern synchrony with those of luteinizing hormone and estradiol in young women (21). In addition, leptin is related to growth hormone (GH), and GH replacement may increase leptin pulsatility (3,31). Furthermore, insulin has been implicated in the physiological regulation of leptin independently of changes in body composition (16,33).…”
mentioning
confidence: 99%
“…In the whole dataset, 24-h leptin levels were the principal correlates of 24-h GH levels and they changed consensually following weight loss. Several authors 35,36 have reported that GH supplementation in GH-deficient adult patients decreased both body fat and plasma leptin concentrations. Moreover, Isokazi et al 37 showed in Zucker fa/fa rats that GH directly inhibits leptin gene expression in visceral fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin secretion may have an Integrative physiology of human adipose tissue KN Frayn et al ultradian pattern 160,161 and show pulsatility with a periodicity of less than 1 h. 162 For such leptin pulsation, it has been suggested that growth hormone pulsation is the pacemaker, 163 but this remains to be proven. Systemic plasma NEFA and glycerol concentrations show pulsatility, 164 as does lipolysis in omental adipose tissue in dogs, arguing for coordinated action of adipose tissue throughout the body.…”
Section: Pulsatilitymentioning
confidence: 99%